The Acceptance Model of QR Code Payment Systems in Thailand: A Proposed Model - Benjaporn Witchutawon; Wornchanok Chaiyasoonthorn; Singha Chaveesuk (My University, 2019)
Technological developments have been playing an important role in the economic system of countries.In order to further propel the Thailand economic system, the government has a national e-payment master plan to support standardized e-payment systems conforming to existing technology.The QR code payment system is one of the national e-payment master plan which the government is trying to push to take Thailand into a cashless society.QR code payment system for citizens in Thailand is very new technology and yet does not have many users.Thus, the purpose of this research is to develop the conceptual framework on QR code payment system in Thailand to initially identify relevant factors which influence the intention to use it for making payments.The research framework has been developed by integrating the Unified Theory of Acceptance and Use of Technology (UTAUT) with trust, perceived risk (PR) and personal innovativeness in information technology (PIIT).Finally, the contribution of this study provides potential factors that could affect the acceptance of QR code payment systems in Thailand.
Keywords: Code (set theory); QR Code Applications and Technologies